1987
DOI: 10.1007/bf00377566
|View full text |Cite
|
Sign up to set email alerts
|

The effect of canopy filtered light on the growth of white clover Trifolium repens

Abstract: Plants of white clover (Trifolium repens) were grown under canopies of clover leaves floating on shallow glass tanks of water and their growth was compared with that of plants under canopies of black polythene 'leaves'. The experimental design allowed the growth of the clover plants in canopy filtered light to be compared with that in unfiltered light at different intensities of Photosynthetically Active Radiation (P.A.R.). The effect of canopy filtered light was to exaggerate the effects of reduced P.A.R. esp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
39
0
1

Year Published

1992
1992
2004
2004

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 115 publications
(47 citation statements)
references
References 15 publications
7
39
0
1
Order By: Relevance
“…Quantitative genetic variation in shade avoidance responses can also be detected directly by examining responses to artificial selection. Several recent studies have detected genetic variation in R:FR responses in wild plant species (Solangaarachchi & Harper 1987;Skavlova & Krahulec 1992;K. Donohue & J. Schmitt, unpublished results).…”
Section: Genetic Variation Within Natural Populationsmentioning
confidence: 99%
“…Quantitative genetic variation in shade avoidance responses can also be detected directly by examining responses to artificial selection. Several recent studies have detected genetic variation in R:FR responses in wild plant species (Solangaarachchi & Harper 1987;Skavlova & Krahulec 1992;K. Donohue & J. Schmitt, unpublished results).…”
Section: Genetic Variation Within Natural Populationsmentioning
confidence: 99%
“…Resource availability might potentially modulate shade avoidance responses because branch initiation and leaf growth are known to respond positively to nutrient availability (Corre! , 1983 ;Marriott & Zuazua, 1996), but negatively to reduced PFD (Solangaarachchi & Harper, 1987 ;Methy et al, 1990). Potential interactions between the R : FR and resource availability, including PFD and soil volume, have not received much attention, especially in grasses (but see Casal et al (1986) and Novoplansky (1991)).…”
Section: mentioning
confidence: 99%
“…Many studies have indicated that the morphological changes of plants induced by the presence of taller neighbours are triggered by alterations in R:FR ratio (e.g., Siegelman & Hendricks 1964;Kasperbauer 1971;Smith 1982). Lower R:FR ratio increased the stem extension rate and the elongation of other above ground organs of plants such as petioles and leaves (Lecharny & Jacques 1979;Morgan et al 1980;Robin et al 1992), and reduced branching of clover and tillering of grass (Solangaarachchi & Harper 1987;Deregibus et al 1983). In this study, the significant difference in R:FR ratio at 10 mm above ground between treatments (Table 4), and the negative correlation between R:FR ratio at 10 mm and the internode length of white clover (r = 0.77, Fig.…”
Section: Stolon Growth Behaviour and Light Qualitymentioning
confidence: 99%